An Optimized Experimental Methodology for L-Band Signal Propagation Sentences Evaluation - Abba, I.; Abidin, W.A.W.Z; Pai, B.V. (IEEE, 2018)
Combining external patch antenna with Global Positioning System (GPS) portable device is necessary to control raw data quality degradation bonded with low signal strength when receiver is operating at low elevation angle. However, this work has designed an economic data collection system comprising developed adaptive graphical user interface and antenna gain enhancement module that manage the open sky GPS propagation data and characterize the signal-to-noise (SNR) as function of elevation and azimuth angles. The model which will used to characterize received SNR mobile satellite (MS) at Kano and Samarahan, show betterquality signal strength with the other one without external patch antenna, thus provide better services to MS users for this environment